Cable modem traffic jam. - Ciciora, W.S (IEEE spectrum)
Broadband access to the Internet by cable modem promises users lightning-fast download speeds and an always-on connection. Recent converts to broadband from dial-up technology are thrilled with complex Web screens that download rapidly. Here, the author describes how tie-ups that slow broadband Internet access to a crawl are a reality-but solutions are also near at hand